Effect of Sodium Hydroxide Treatment on Adsorption of Methylene Blue Based on Cellulose Nano Crystals - Mustikaningrum, Mega; Adelina, Dina; Indrawati Sawali, Fikrah Dian; Afandy, Moh Azhar (Vocational College of Universitas Diponegoro, 2024)
Methylene blue is one of the dye wastes that dissolve in the aquatic environment that cannot be directly degraded by the environment. If the quantity of this waste is large, it will become a compound that is toxic to the aquatic environment. One of the modern methods used to process this dye waste is adsorption. The adsorption method is a method of binding compounds with the help of adsorbents. One of the renewable adsorbent technologies comes from cellulose. Cellulose is often used because it has active groups that are quite effective in binding certain compounds. In this study, cellulose IV was produced, called nano cellulose crystals. Cellulose generally consists of amorphous and crystalline parts. The cellulose produced is hydrolyzed with sulfuric acid to remove the amorphous part so that only crystalline cellulose is obtained, followed by the help of ultrasonic waves to break the size into a nano form which is expected to have a large surface area. As a result of the hydrolysis stage, the nano cellulose crystals produced have sulfate groups that can bind methylene blue which when dissolved in water becomes cationic. This force is called electrostatic force. Some important stages of cellulose nanocrystal production are alkaline treatment, bleaching, hydrolysis, sonication, and freeze-drying. This study focuses on the effect of NaOH concentration used in alkaline treatment. NaOH in this case functions to dissolve impurities such as hemicellulose and lignin in a biomass. Removal of hemicellulose and lignin greatly affects the yield of cellulose produced. Based on the results of the study using 3,4, and 5% NaOH produced cellulose percentages of 38.7121; 39.7949, and 39.9138%, respectively. Cellulose content ultimately affects the number of active groups that bind methylene blue. The adsorption study evidences this obtained the percentage of removal at each concentration of 67.685; 70.837 and 71.823%. Another objective of this study was also to get the constant value of the extraction rate at each NaOH concentration used in the adsorption process. The values obtained were 0.0029; 0.0032 and 0.0039 m/minute at each NaOH concentration used during the alkaline treatment process.